Lactobacillus reuteri ZJ617 Culture Supernatant Attenuates Acute Liver Injury Induced in Mice by Lipopolysaccharide. Issue 11 (1st June 2019) - Cui, Yanjun; Qi, Sirui; Zhang, Wenming; Mao, Jiangdi; Tang, Renlong; Wang, Chong; Liu, Jianxin; Luo, Xin M; Wang, Haifeng
ABSTRACT: Background: Lactobacillus rhamnosus GG culture supernatant (LGGs) promotes intestinal integrity and ameliorates acute liver injury induced by alcohol in mice. Objectives: The aim of this study was to investigate the protective effects and molecular mechanisms of Lactobacillus reuteri ZJ617 culture supernatant (ZJ617s) on acute liver injury induced by lipopolysaccharide (LPS) in mice. Methods: Male C57BL/6 mice (20 ± 2 g, 8 wk old) were randomly divided into 4 groups (6 mice/group): oral inoculation with phosphate-buffered saline (control), intraperitoneal injection of LPS (10 mg/kg body weight) (LPS), oral inoculation with ZJ617s 2 wk before intraperitoneal injection of LPS (ZJ617s + LPS), or oral inoculation with LGGs 2 wk before intraperitoneal injection of LPS (LGGs + LPS). Systemic inflammation, intestinal integrity, biomarkers of hepatic function, autophagy, and apoptosis signals in the liver were determined. Results: Twenty-four hours after LPS injection, the activities of serum alanine transaminase and aspartate transaminase were 32.2% and 30.3% lower in the ZJ617s + LPS group compared with the LPS group, respectively ( P < 0.05). The ZJ617s + LPS group exhibited higher intestinal expression of claudin 3 (62.5%), occludin (60.1%), and zonula occludens 1 (60.5%) compared with the LPS group ( P < 0.05). The concentrations of hepatic interleukin-6 and tumor necrosis factor-α were 21.4% and 27.3% lower in the ZJ617s + LPS group compared with the LPS group, respectively ( P < 0.05). However, the concentration of interleukin-10 was 22.2% higher in the ZJ617s + LPS group. LPS increased the expression of Toll-like receptor 4 (TLR4; by 50.5%), phosphorylation p38 mitogen-activated protein kinase (p38MAPK; by 57.1%), extracellular signal-regulated kinase (by 77.8%), c-Jun N-terminal kinase (by 42.9%), and nuclear factor-κB (NF-κB; by 36.0%) compared with the control group. Supplementation with ZJ617s or LGGs ameliorated these effects ( P < 0.05). Moreover, the hepatic expression of active caspase-3 and microtubule-associated protein 1 light chain 3 II was 23.8% and 28.6% lower in the ZJ617s + LPS group compared with the LPS group, respectively ( P < 0.05). Conclusions: ZJ617s exerts beneficial effects on the mouse liver through suppression of hepatic TLR4/MAPK/NF-κB activation, apoptosis, and autophagy. This trial was registered at Zhejiang University (http://www.lac.zju.edu.cn ) as NO.ZJU20170529.